STUDY OF CEREBROTROPIC DOSE-DEPENDENT EFFECT OF PYRIMIDINE DERIVATIVE UNDER PIR-9 CODE AGAINST THE BACKGROUND OF EXPERIMENTAL CEREBRAL ISCHEMIA IN RATS - A. V. Voronkov; N. B. Shabanova; M. P. Voronkova; T. A. Lysenko (Фармация и фармакология (Пятигорск), 2019)
Nowadays, the incidence of cerebrovascular disease is steadily increasing. Disorders of cerebral circulation contribute to the increase in the degree of mortality, disability, and incapacitation of the population. An extensive arsenal of drugs with cerebroprotective effects does not satisfy clinical specialists. In this connection, there is an obvious need for new compounds exhibiting cerebroprotropic properties, as well as those able of improving the prognosis of the course of ischemic genesis pathologies.The aim of the article is to study the dose-dependent cerebrotropic effect of a pyrimidine derivative under PIR-9 code against the background of experimental cerebral ischemia in rats.Materials and methods. The experiment was conducted on 140 male Wistar rats (m=170–190 g) divided into 7 equal groups. Pyrimidine derivative PIR – 9 (25, 50 and 100 mg/kg), Vinpocetine (3.2 mg/kg) and Cinnarizine (5.6 mg/kg) suspension of purified water and Tween-80 were used as the studied substances. Experimental cerebral ischemia was reproduced by irreversible occlusion of common carotid arteries (chloral hydrate anesthesia – 350 mg/kg). Experimental substances, reference preparations and purified water were administered prophylactically within 10 days before surgery. One day later the survival, neurological deficiency, behavioral activity, changes in cognitive-mnestic functions, as well as some indicators of brain energy exchange were evaluated.Results. In an experimental study of the cerebrotropic effect of the substance under PIR-9 code (pyrimidine-4-(1H)-one derivative) in various dosages against the background of irreversible occlusion of the common carotid arteries, a decrease in neurological, behavioral, mnestic and cognitive defects has been established. Hereby, the best effect was observed against the background of the administration of the compound PIR-9 at the dose of 50 mg kg. In addition, the prophylactic administration of the test substance PIR-9 (50 mg/kg) has shown the improvement of the energy metabolism in the postischemic period.Conclusion. In the course of the study it was established that the substance under the laboratory code PIR-9 exhibited the most pronounced cerebroprotective effect at the dose of 50 mg/ kg, which was not inferior in its strength to the reference drug Cinnarizine and exceeding Vinpocetine.